Qashidah Burdah sebagai Media Pengobatan Magis-Ekonomis: Studi terhadap Tradisi Pembacaan Qashidah Burdah terhadap Orang Sakit di Desa Sera Timur Kecamatan Bluto Kabupaten Sumenep Propinsi Jawa Timur - Faidi, Ahmad (MILLATI: Journal of Islamic Studies and Humanities, 2016)
The tradition of Qashidah Burdah reading againsts sick people carried out at the EastÂ Sera village is different from the other regions. The difference is the aim of the practiceÂ which is more specific and focus to cure disease. It indicates that the tradition ofÂ Qashidah Burdah reading carried out at the East Sera village has meaning and functionÂ specifications which can not be found in other areas. East Sera society interpret QashidahÂ Burdah tradition as an alternatif treatment media implemented when the other mediaÂ treatments (medical and shaman) are not able to cure. In addition, the tradition ofÂ Qashidah Burdah reading againsts sick person also has several functions; namely socio-economic function (this media treatment is much cheaper than the others); socio-religiousÂ function (it can strengthen monotheism, fortitude and resignation to Allah), and socio-cultural function as a medium for preserving helpfulness attitude, familiarity, and socialÂ solidarity. The existence of those functions â both latent and manifest â becomes theÂ reason of why the tradition of Qashidah Burdah reading againsts sick people stillÂ continues to be preserved by the people of East Sera.